Les nouveautés du système comptable algérien des sociétés d’assurances et/ou de réassurances News of the Algerian accounting system for insurance and/or reinsurance companies. - Mohamed DEBBOUZINE (المجلة الدولية للأداء الاقتصادي, 2023)
This article aims to present the novelties brought to the accounting of insurance and reinsurance organizations in Algeria, and this, within the framework of the new regulations enacted by the Notice N ° 89 of the CNC, of March 10, 2011. The most significant change is the removal of the concept "Technical debts" which have been replaced by class 03 "accounts for technical insurance reserves".